Comparative evaluation of 2 pulsed field ablation systems for atrial fibrillation: insights from real-world clinical implementation and short-term outcomes - Zylla, Maura Magdalena; Mages, Christine; Rahm, Ann-Kathrin; Wiedmann, Felix Tobias; Schweizer, Patrick Alexander; Thomas, Dierk; Frey, Norbert; Lugenbiel, Patrick (Heart rhythm, 2025)
Background - Pulsed field ablation (PFA) is a safe and effective technology for catheter ablation of atrial fibrillation (AF). Multiple PFA-platforms for AF ablation have been developed. However, evidence comparing the real-world implementation and performance of different PFA systems is still limited. - Objective - This study compares procedural and acute outcome parameters during implementation of the PFA system employing a pentaspline PFA catheter (FARAPULSE, Boston Scientific, Marlborough, MA) and a platform using a circular PFA-catheter (PulseSelect, Medtronic, Minneapolis, MN). - Methods - The first consecutive 40 patients treated with each PFA system were included. Baseline characteristics, procedural parameters, and short-term outcome regarding periprocedural safety and efficacy were evaluated. - Results - The majority of patients showed paroxysmal AF, nearly one-third of patients in both groups suffered from persistent AF. Overall procedural complication rates were not different among subgroups (circular catheter: 12.5%; pentaspline catheter: 7.5%, P = .71), mainly minor (circular catheter: 10.0%; pentaspline catheter: 7.5%, P =1.00). There was no significant difference in median procedure duration (circular catheter: 42.0 minutes; pentaspline catheter: 43.0 minutes, P = .292), left atrial (LA) dwell time (circular catheter: 29.0 minutes; pentaspline catheter: 31.0 minutes, P = .623), and fluoroscopy duration (circular catheter: 13.2 min; pentaspline catheter: 11.9 minutes, P = .132). With the pentaspline PFA catheter, no learning curve was observed regarding procedural parameters over the course of 40 procedures. With the circular PFA catheter, there was a statistically significant decrease in LA dwell time and fluoroscopy duration comparing the first and last 10 procedures. - Conclusion - Both PFA systems could be safely and rapidly implemented into clinical practice of an experienced center. Large-scale clinical trials are needed to compare long-term outcome between different PFA systems currently introduced into clinical practice.
Online veröffentlicht: 7. November 2024, Artikelversion: 3. September 2025
Gesehen am 10.12.2025